An Error Analysis in Writing Descriptive Text of The Tenth Grade Students - Alisa, Siti Nur; Apsari, Yanuarti (IKIP Siliwangi, 2025)
Writing is one of the most challenging skills to master because it needs various sub-skills to produce a good and correct written product. Without mastering these sub-skills, the results of the writing activity will include a variety of errors. This research aims to determine what types of errors occur and most often appear in writing descriptive texts. The qualitative method was utilized to answer the research questions in this research. This research was conducted in MAS Al-Bidayah Batujajar. The samples of this study were 34 students of class X MIPA. The data was collected from the written test. The result shows that there were four types of errors made by the students. They are Omission, Addition, Misinformation, and Misordering error. The frequency of each type of error is different. As for if sorted from the highest frequency to the lowest frequency is as follows: first is Misinformation error (39.82%), second is Addition error (37.17%), third is Omission error (21.24%), and fourth is Misordering error (1.77%).